QoS based spectrum decision framework for cognitive radio networks - Mishra, Vishram (2013)
Recently cognitive radio has gained considerable interest by wireless communication researchers as a viable mean to solve the spectrum utilization problem. The advancement in this area has met with many challenges including in the field of spectrum decision. To this end we propose a QoS based spectrum decision framework for cognitive radio networks which guarantees the QoS to the data packets by allocating the channel which can satisfy the QoS requirement. This is done by categorizing the data packets and channels and then by providing a mapping between them. Four levels of packet priority is supported with this framework. Performance analysis is done to show the effectiveness of the proposed framework.